Using EGRA Technique to Improve Students' Grammar Mastery - Wulandari Dwi; Amzah (Institut Agama Islam Negeri Parepare, 2021)
Grammar is study of rules that cover the combination of words to form meaningful and grammatically correct sentence. This study use Experience, Generalization, Reinforcement, and Application (EGRA) technique to improve students` grammar mastery. By using this technique the students try to find out the form and function of the sentence by themselves. Besides that, EGRA technique has various instructions to help students understand the material; giving picture, vocabularies and quiz in experience step, analyzing the text in generalization step, providing in reinforcement step, and giving a task in application step. This study was aimed to see the Improving Grammar Mastery at the tenth grade students of SMA Negeri 7 Pinrang. The objective of this study is to get the empirical data of the differences between students` score grammar test that were taught by using EGRA technique and the students were not. The population of this study consists of 273 students. The sampling process of this research is cluster random sampling technique. The researcher took two classes, X MIPA 2 as experimental class consisted of 36 students and X IPS 2 as control class consisted of 34 students. The design of this study is a quantitative method using quasi-experimental design (non-equivalent control group) with two group classess, namely experimental class and control class. The data was collected through pretest and posttest. It aimed to know whether the EGRA technique in teaching grammar can improve students` grammar mastery. The result of this research shows that students` grammar mastery significantly improves. Based on the calculation, the result of the data analysis by using t-test showed the value of ttest (to) was higher than ttable (tt), to > tt = 9.11 > 1.667, in significant degree of 0.05 (5%). As the statistical hypotheses shows, if ttest (to) > ttable (tt) in significant degree of 0.05 (5%), it means that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. In conclusion, EGRA technique is able to improve the students` grammar mastery.